Pengaruh Etika Kerja, Etika Bisnis Dan Etos Kerja Terhadap Persaingan Entrepreneur Pada Organisasi Perkumpulan Perempuan Wirausaha Indonesia Dewan Pimpinan Cabang Kabupaten Banyuwangi - Muhammad Syarofi (INAIFAS Press, 2020)
Work ethics as a critical and rationalist reflection on moral values ​​and norms in determining attitudes and behavior of human life, as well as business ethics values ​​that will encourage values ​​of goodness, and actualized morality in human behavior, as well as work ethic values ​​that promote the totality of personality. someone in encouraging himself to act and achieve good deeds so that the relationship between humans can be well established, in social and economic behavior in running his business which does not rule out competition between entrepreneurs with one another. This study aims to examine empirically the variables in the research that have been formulated in the formulation of the problem, namely whether work ethics, business ethics and work ethics have a significant effect on thecompetition of entrepreneurial members female entrepreneurialof DPC Banyuwangi, simultaneously and partially. This research is in the form of quantitative explanatory research to analyze the effect of work ethics, business ethics and work ethics oncompetition entrepreneurial, using a survey method. Sampling using sampling techniques nonprobability Sampling withtechnique sampling the most appropriateis saturated sampling pursuant to which all members of the DPC Banyuwangi women entrepreneurs numbering as many as 49 people. Multiple linear regression analysis tools, with the help of Statistical Package for the Sciences (SPSS) software version 22. The results of the analysis show that work ethic variables have a significant effect oncompetition entrepreneurial, with (Standardized Coefficients) 0.092. The variable of business ethics has a significant effect oncompetition entrepreneurial, with (Standardized Coefficients) 0.081. Work ethic variable has a significant effect oncompetition entrepreneur, with (Standardized Coefficients) 0.864. Meanwhile, (Simultaneously) work ethics, business ethics and work ethic variables have a significant effect oncompetition entrepreneurial with a calculated F value of 724.101 ≥ F table 3.20 and a significance of 0.000 ≤ 0.05. Then to test R2 (coefficient of determination) amounted to 0,990, or 99%, while the remaining 1% is influenced by other variables not examined by the authors in this study. Etika kerja sebagai refleksi kritis dan rasionalis mengenai nilai moral dan norma dalam menentukan sikap dan perilaku hidup manusia, sekaligus nilai etika bisnis yang akan mendorong nilai-nilai kebaikan, dan moralitas yang diaktualisasikan dalam perilaku manusia, begitu juga nilai etos kerja yang mengedepankan totalitas kepribadian seseorang dalam mendorong dirinya untuk bertindak dan meraih amal kebajikan sehingga hubungan antara manusia dapat terjalin dengan baik baik, dalam perilaku sosial dan ekonomi dalam menjalankan usahanya yang tidak menutup kemungkinan akan terjadinya persaingan antara entrepreneur satu dengan yang lainnya. Penelitian ini bertujuan untuk mengkaji secara empiris variabel-variabel dalam penelitian yang telah dirumuskan dalam rumusan masalah yaitu apakah etika kerja, etika bisnis dan etos kerja berpengaruh signifikan terhadap persaingan entrepreneur anggota wirausaha perempuan DPC Banyuwangi, secara simultan dan parsial. Penelitian berbentuk kuantitatif explanatory research untuk menganalisis pengaruh etika kerja, etika bisnis dan etos kerja terhadap persaingan enterpreneur, dengan metode survei. Pengambilan sampel menggunakan tekhnik sampling Nonprobability Sampling dengan teknik sampling yang paling cocok adalah sampling jenuh yaitu seluruh anggota wirausaha perempuan DPC Banyuwangi yang berjumlah sebanyak 49 orang. Alat analisis regresi linier berganda, dengan bantuan software Statistical Package for the Sciences (SPSS) versi 22. Hasil analisis menunjukkan variabel etika kerja berpengaruh signifikan terhadap persaingan entrepreneur, dengan (Standardized Coefficients) 0,092. Variabel etika bisnis berpengaruh signifikan terhadap persaingan entrepreneur, dengan (Standardized Coefficients) 0,081. Variabel etos kerja berpengaruh signifikan terhadap persaingan entrepreneur, dengan (Standardized Coefficients) 0,864. Sedangkan (Simultan) variabel etika kerja, etika bisnis dan etos kerja berpengaruh signifikan terhadap persaingan entrepreneur dengan nilai F hitung sebesar 724,101 ≥ F tabel 3,20 dan Signifikansi 0,000 ≤ 0,05. Kemudian untuk uji R2 (koefisien determinasi) sebesar 0,990 atau 99%, sedangkan sisanya sebesar 1% dipengaruhi oleh variabel lain yang tidak diteliti oleh penulis dalam penelitian ini